Character association and path analysis among yield components in castor (Ricinus communis L.): CHARACTER ASSOCIATION AND PATH ANALYSIS AMONG YIELD COMPONENTS IN CASTOR - S KRISHNA CHAITANYA; O VENKATESWARLU; M REDDI SEKHAR; B V BHASKARA REDDY (Journal of Oilseeds Research, 2013)
The analysis of the nature and magnitude of associations among 10 quantitative traits and their contribution towardsseed yield was carried out in 30 genotypes of castor (Ricinus communis L.) during the winterseason of 2009 at Regional Agricultural Research Station, Tirupati. The results revealed that 1200 seed weight, oil yield/plant, effective length of main spike, oil content and number ofspikes/plant had significant positive association with seed yield/plant. Path analysis revealed that oil yield/plant, 100 seed weight, number of capsules on main spike, number of nodes upto main spike, plant height up to main spike and days to 50% flowering are the direct contributors for seed yield in castor.